СИМВОЛ КАК ОБРАЗНОЕ СРЕДСТВО ХУДОЖЕСТВЕННОЙ РЕЧИ - Абдалиева, Г.Р. (SCIENCE and SOCIETY, 2021)
This article examines the use of symbol as a figurative means of artistic speech in the text of the novel “Maman biy epic” by T. Kaipbergenov.